2013
DOI: 10.1007/s00018-012-1242-8
|View full text |Cite
|
Sign up to set email alerts
|

Immobile survival of motoneuron (SMN) protein stored in Cajal bodies can be mobilized by protein interactions

Abstract: Reduced levels of survival of motoneuron (SMN) protein lead to spinal muscular atrophy, but it is still unknown how SMN protects motoneurons in the spinal cord against degeneration. In the nucleus, SMN is associated with two types of nuclear bodies denoted as gems and Cajal bodies (CBs). The 23 kDa isoform of fibroblast growth factor-2 (FGF-2(23)) is a nuclear protein that binds to SMN and destabilizes the SMN-Gemin2 complex. In the present study, we show that FGF-2(23) depletes SMN from CBs without affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Interestingly, it was shown that the release of SMN from CBs by FGF-2 expression leads to an accumulation of Sm proteins and U4 snRNA in CBs ( 63 ). According to our model, this might result from a defect in the assembly of U4-specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that the release of SMN from CBs by FGF-2 expression leads to an accumulation of Sm proteins and U4 snRNA in CBs ( 63 ). According to our model, this might result from a defect in the assembly of U4-specific proteins.…”
Section: Discussionmentioning
confidence: 99%
“…SMN (survivor of motor neuron) is mutated in most cases of spinal muscular atrophy (SMA), and plays a crucial role in the cytoplasmic phase of snRNP biogenesis. The role of SMN in the CB is less clear, but may involve snRNA regeneration (Pellizzoni et al, 1998) and/or tri-snRNP assembly (Boulisfane et al, 2011, Forthmann et al, 2013). Coilin is known as the CB marker protein and is essential for canonical CB formation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma SK-N-BE(2) cells were differentiated for different periods with retinoic acid (5 µM), lysed by sonification in modified RIPA-buffer [7] and analyzed by Western blot for coilin, SMN and α-Tubulin (A). (B) Endogenous coilin protein levels were decreased significantly to 52% after 72h of differentiation, (C) while SMN protein levels were increased non-significantly after the same time of differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Immunocytochemistry and fluorescence microscopy were performed as described previously [7]. Antibodies used were anti-coilin (H-300, rabbit IgG, Santa Cruz), anti-SMN (mouse IgG, BD Bioscience), anti-α-tubulin (mouse IgG, Santa Cruz) and secondary antibodies Alexa Fluor® 488 goat anti-mouse IgG, Alexa Fluor® 555 goat anti-mouse IgG and Alexa Fluor® 555 goat anti-rabbit IgG (Invitrogen) or anti-mouse peroxidase-linked (sheep, Amersham) and anti-rabbit peroxidase-linked (goat IgG, Jackson ImmunoResearch).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation